Controlling precipitation of value added zirconia - Carter, Geoffrey A. (Curtin University, 2009)
Advanced zirconia-based materials have many important applications in electronics and medical applications, and of most interest to this research, solid oxide fuel cells (SOFC) which is a key technology for alternative and hydrogen-based energy generation. The SOFC in its most basic form is a device for converting hydrogen and oxygen into water with a resulting generation of power. Most SOFC manufacturers/developers are using zirconia doped with yttria as the electrolyte with variations on the amount of yttria. The SOFC places high demands on the ceramic components, placing significant demands on powder processing technology to enable fabrication of reliable components. It has been shown that the process of co-precipitation of three initially mixed chlorides, aluminium chloride, yttrium chloride and zirconium oxychloride in aqueous solutions, can produce an oxide powder that can be used in SOFC manufacture. Zirconia powders synthesised from aqueous solution in this way have been found, however, to include hard agglomerates which are detrimental to further processing and applications.Industrial manufacture of zirconia and zirconia-yttria products can best be summarised as four step operation; (1) hydrolyse of zirconyl chloride and mixing of other solutions, (2) precipitation, (3) calcination (4) forward processing for particle size, surface area and handle-ability characteristics . The use of aqueous solutions allows for lower costs of production and reduced waste. However such production is hampered by limited understanding of the fundamental chemistry particularly during aqueous processing which limits the development of better powders for the widespread use of SOFC’s. The aim of this project was to develop an understanding of these problems based on an industrial process that is in use within Western Australia. The work has been broken up into five sections, with the first four dealing with predominately non-stabilized zirconia and tracks the process from aqueous chemistry through to final ceramic. The final section does the same for a 3 mole% yttrium partially stabilised zirconia.The influence of concentration and added chloride salts on the solution speciation of zirconyl chloride solutions, and the precipitate formed upon addition of aqueous ammonia, has been investigated using a combination of techniques, such as SAXS, DLS, ICP-OES, TEM and SEM.To further investigate the precipitation process the effect of pH of precipitation, starting solution concentration, and agitation levels on the particle size of hydrous zirconia precipitates have been investigated. The pH of precipitation was also found to have a significant impact on the type of hydrous zirconia produced. TGA/DTA, micro combustion and TEM / EDS were used to investigate the difference in the powders produced at pH 3 and 12.The two hydrous zirconium manufactured at pH 3 and 12 have been studied as further processing consistent with industrial procedures was undertaken, including how the differences in structure due to the pH of precipitation, may effect the calcination, in situ and ex situ x-ray diffraction was used for this.With the knowledge developed thus far, two 3 mol% partially stabilised zirconia (P-SZ) samples suitable for the SOFC market were manufactured from solutions through to ceramics.The combination of SAXS, DLS, in situ XRD, TEM, ICP, TGA/DTA, micro combustion, and standard ceramic testing was found to be excellent for providing comprehensive information on changes through an industrial process and will allow optimisation to produce powders suitable for SOFC applications.